2016
DOI: 10.1063/1.4954046
|View full text |Cite
|
Sign up to set email alerts
|

Application of classical thermodynamics to the conductivity in non-polar media

Abstract: Articles you may be interested inElectrical conductivity in non-polar media is a subject which recently regained interest. If most of experiments and theoretical developments were done more than 50 years ago, new experiments and theories have been recently published. As the electrical conductivity describes, at low field, the equilibrium state of a system, it is natural to apply theories based on equilibrium thermodynamics. In this article, well-established classical thermodynamics and solvations models are ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In [12] a theory on the conductivity in non-polar medium was proposed. This theory predicted the dependence of the conductivity on the dielectric permittivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [12] a theory on the conductivity in non-polar medium was proposed. This theory predicted the dependence of the conductivity on the dielectric permittivity.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, the chemical potential of the ionogenic species is not a¤ected by the creation of ions or of ion-pairs. We have recently proposed a theory for the conductivity of these systems based on classical thermodynamics [12]. We refer to this article for further details about the derivations and discussions about the applicability of alternative theories.…”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent investigation of toluene mixtures with several different alcohols, Dukhin and Parlia [33] suggested that electrical conductivity depends on the concentration of ion pairs, which varies with the dielectric constant of the mixtures. However, others have subsequently questioned these explanations, on the grounds that they do not adhere to classical thermodynamics [34,35]. In addition, Gourdin-Bertin and Chassagne [34] reasoned that autoprotolysis would not account for the observed electrical conductivity behavior because only very low concentrations of ionic species would be present.…”
Section: Electrical Conduction In Non-aqueous Liquidsmentioning
confidence: 99%
“…However, others have subsequently questioned these explanations, on the grounds that they do not adhere to classical thermodynamics [34,35]. In addition, Gourdin-Bertin and Chassagne [34] reasoned that autoprotolysis would not account for the observed electrical conductivity behavior because only very low concentrations of ionic species would be present. Moreover, the role of composition-dependent ion pairing was also questioned [34].…”
Section: Electrical Conduction In Non-aqueous Liquidsmentioning
confidence: 99%
See 1 more Smart Citation